The potential of river utilization as public health leverage in Indonesia - Suprayogi, Dedy (International Conference on Sustainable Health Promotion, 2018)
Rivers has tremendous benefits for human life generally and for Indonesian’s health and wellbeing’s society in particular. One of them is the function of the river to support peoples who live in the watershed. However, river basin could become health menace if not well maintained, for example, the flood that might be caused by silting of the river as the impact from littering. Public health is not only measured by the high rates of morbidity in an area but can also be triggered by extraordinary events or disasters such as floods. This paper was made to analyze the ability of the river as a community health leverage through identification and review of various articles. Based on extensive article reviews, this study was found that disease prevention and environmental control were the two main factors that could be the foundation of levers public health degrees. Therefore, it is essential to prevent transmissions of infectious diseases and to maintain a sustainable environment.